Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Simetri Putra Perkasa - Whina Ratnawati; Rio Setiawan; Laila Irawati (Universitas Medan Area, 2022)
This study aims to determine the effect of motivation and work discipline on employee performance at PT. Simetri Putra Perkasa (SPP) Tangerang. The population in this study were employees in the metal division at PT. Simetri Putra Perkasa totaling 101 people, the sample technique used is to use the slovin formula to 50 people, the data collection technique used in this study is a questionnaire/questionnaire method. Analysis of the data used in this study using multiple linear regression analysis. The results showed that motivation had a significant effect on performance, while work discipline also had a significant effect on performance. The results of simultaneous hypothesis testing show that motivation and work discipline simultaneously have a significant effect on employee performance. The coefficient of determination test obtained the coefficient of determination (R-Square) of 0.830, it can be concluded that motivation (X1) and work discipline (X2) have an influence contribution of 83% on employee performance. Companies need to increase motivation and work discipline to improve the performance of employees of PT. Simetri Putra Perkasa.